Thinking like a mountain : Aldo Leopold and the evolution of an ecological attitude toward deer, wolves, and forests - Flader, Susan (Book collections on Project MUSE., 1994)
"When initially published more than twenty years ago, Thinking Like a Mountain was the first of a handful of efforts to capture the work and thought of America's most significant environmental thinker, Aldo Leopold. This new edition of Susan Flader's masterful account of Leopold's philosophical journey, including a new preface reviewing recent Leopold scholarship, makes this classic case study available again and brings much-deserved attention to the continuing influence and importance of Leopold today. Thinking Like a Mountain unfolds with Flader's close analysis of Leopold's essay of the same title, which explores issues of predation by studying the interrelationships between deer, wolves, and forests. Flader shows how his approach to wildlife management and species preservation evolved from his experiences restoring the deer population in the Southwestern United States, his study of the German system of forest and wildlife management, and his efforts to combat the overpopulation of deer in Wisconsin. His own intellectual development parallels the formation of the conservation movement, reflecting his struggle to understand the relationship between the land and its human and animal inhabitants. Drawing from the entire corpus of Leopold's works, including published and unpublished writing, correspondence, field notes, and journals, Flader places Leopold in his historical context. In addition, a biographical sketch draws on personal interviews with family, friends, and colleagues to illuminate his many roles as scientist, philosopher, citizen, policy maker, and teacher. Flader's insight and profound appreciation of the issues make Thinking Like a Mountain a standard source for readers interested in Leopold scholarship and the development of ecology and conservation in the twentieth century." --